Impact of muscle mass loss assessed by computed tomography on the outcome of allogeneic stem cell transplantation. Issue 7 (7th June 2022) - Nagayama, Takashi; Fujiwara, Shin-ichiro; Kikuchi, Tomohiro; Onda, Kaoru; Murahashi, Rui; Nakashima, Hirotomo; Ikeda, Takashi; Matsuoka, Sae; Kawaguchi, Shin-ichiro; Toda, Yumiko; Ito, Shoko; Ban, Tetsuaki; et al.
Abstract: The definition of sarcopenia assessed by computed tomography (CT) varies among different reports, and few studies have examined the effect of muscle mass loss on the prognosis of post-hematopoietic cell transplantation (HCT). We retrospectively evaluated 172 patients who underwent an initial allogeneic HCT for acute leukemia at our institution. They were divided into 3 groups according to muscle mass measured at the third lumbar vertebra as assessed by CT. Patients with low muscle mass had a worse performance status, higher comorbidity index and higher disease risk. There was a significant difference in 2-year overall survival between the 3 groups, and worse overall survival (OS) was associated with lower muscle mass ( p  = 0.005). Muscle mass loss did not affect non-relapse mortality ( p  = 0.238) but was significantly associated with relapse ( p  = 0.067). Pre-transplant muscle mass loss may therefore reflect a poor prognosis for the primary disease.